Extrato líquido padronizado em capsantina a partir de Capsicum chinense Jacq. (Variedade Biquinho) e suas aplicações no desenvolvimento de um produto cosmético anti-aging - Brito, Lucélia de Sousa (2018)
Introduction: The pepper Capsicum chinense Jacq., popularly known as "biquinho pepper", has been outstanding in Brazil for presenting low pungency and a strong aroma. Its fruits are composed of several secondary metabolites, especially carotenoids, with important antioxidant properties. Objective: Develop a cosmetic product from the liquid extract of Capsicum chinense Jacq. standardized on capsanthin, evaluate its anti-aging efficacy in vivo and antioxidant activity. Methodology: The fruits of the "biquinho pepper" were sanitized, weighed, dehydrated, ground in a knife mill and hammers and stored at room temperature. The physico-chemical characterization of the pulverized vegetable raw material was carried out using the methods of microscopic analysis of the powder, determination of the volatile content, total ash, granulometric distribution and swelling index. Afterwards, the raw material was applied in the preparation of the liquid extract, using the techniques of maceration, percolation and concentration by forced ventilation, using the ethyl alcohol 96o GL as solvent extractor. The liquid extract was then characterized for solids content, pH, density and viscosity. Subsequently, total phenol concentration was determined by the technique of complexation of the phenolic compounds with ferric chloride solution, and also, the assay of total flavonoids and carotenoids by spectrophotometric methods. In addition, an analytical method by HPLC was validated for the quantification of the capsanthin in the concentrated liquid extract. Two cosmetics formulations were developed to perform comparative efficacy tests, a phytocosmistry developed from the liquid extract standardized on capsanthin, and another placebo formulation composed only of the galenic base of the product, without the addition of the extract. The cosmetics formulations were then evaluated for their accelerated stabilities and clinical efficacy anti-aging in vivo, evaluated in humans. The antioxidant activity was determined for the vegetable raw material, standardized liquid extract in capsanthin and the cosmetic formulation, using the DPPH radical capture, β-carotene / linoleic acid capture and ABTS radical capture assays. Results and discussion: For the physical-chemical characterization of the pulverized vegetable raw material, the microscopic analysis of the powder demonstrated the intimate nature of the sample as well as its purity, presented a volatile content of 4.62% (m / m), total ash content of 6.341%, the determination of the granulometric distribution classified the sample as coarse powder and the intumescence index was 1.27 ml ± 0.12 using alcohol 96o GL as an intumescent agent. In the physical-chemical characterization of the liquid extract the solids content was 19.16%, pH 3.7 ± 0.06, density 1.040 ± 0.0014 g / mL and viscosity of 3.22 mPas. The total phenolics, flavonoids and carotenoids contents for the raw material and concentrated liquid extract samples were respectively: 18 mg / 100 g and 168 mg / 100 g phenols, 10 mg / 100 g and 90.7 mg / 100 g flavonoids, 10mg / 100g and 83,70 mg / 100g of carotenoids. The validation of the analytical method by HPLC used in the quantification of capsanthin proved to be selective, linear (in the range of 0.48 to 7.2 μg / ml for the capsanthin standard and 26.93 to 404 mg / ml for the liquid extract), accurate, exact and robust. The content of capsanthin found in the liquid extract of C. chinense Jacq. was 1.126% (m / m). Both the standardized liquid extract and the cosmetic formulations were stable against accelerated stability tests, with results of organoleptic and physico-chemical characteristics within the parameters established for the tests. The analysis of the clinical anti-aging efficacy in vivo for cosmetic formulations has demonstrated the potentiation of efficacy for the cosmetic formulation consisting of the standardized liquid extract of Capsicum chinense Jacq., Compared with the placebo cosmetic, showing improvements in wrinkles, expression lines and sagging skin. The antioxidant activity in vitro for the vegetable raw material, standardized liquid extract in capsanthin and cosmetic formulation were respectively: 194.6μg / ml, 73.7μg / ml and 100μg / ml for capturing the DPPH radical relative to the IC50, 33.03%, 42.08% and 19.35% for inhibition of β-carotene oxidation, 22.87 μM Trolox / g, 51.81 μM Trolox / g, 900 μM Trolox / g for the ABTS radical capture. The values obtained for evaluations of antioxidant activities in vitro indicated that all the samples showed to be effective by antioxidant action, although the results have been lower if compared to their respective positive controls. Conclusions: The cosmetic product developed showed antioxidant activity and intended anti-aging efficacy, proving of potential use of the standardized liquid extract of biquinho pepper (Capsicum chinense Jacq.) in technological and innovative phytocosmetic formulations.